A cultural approach to preserving squatter settlements: the case of Treasure Hill Village in Taipei. Issue 4 (3rd April 2022) - Li, Danzhou; Zhong, Shuting; Wang, Qing; Chen, Lifei
ABSTRACT: Based on historical research and on-site fieldwork, this paper probes the historic preservation of Treasure Hill Village, which takes place along with the reproduction of the space of Taipei city and the process of society-making in Taiwan. We argue that culture has been implemented as a contested approach through squatter settlements, which can be successfully preserved as a heritage site. On the one hand, the heritage politics of squatter settlements coincide with Taiwan's turn to polarised politics, which adopts the preservation of a counterhegemonic community to validate the legitimacy of a transitional governance authority from below. On the other hand, Treasure Hill Village, as an artist village in the urban sphere, reveals that neoliberal capitalism has dominated the narrative of urban development for the sake of economic initiatives. Even if art and activism have together attempted to preserve the history of ignored people and reshape the 'lived' cultures under the threat of house dismantlement, we should be alert to the paradoxical rhetoric of culture, as it might damage the declining and marginalised residents' access to heritage. The cultural struggle for the right to Taipei city indicates that the question of 'whose heritage?' remains an unfinished project.